Da Campanha de Educação de Adolescentes e Adultos aos Grupos Escolares noturnos: São Carlos, SP (1930 a 1950) - Fornaciari, Gabriela Maria [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This study is based on the (re) building of night school groups Eudóxia Coelho and Perpétua Genofre from São Carlos/ SP´s history, both institutions created in 1948 determining the beginning of the legal activities of adult education in the municipal district. The period of time studied refers the 1930´s up to 1950´s, being the years that precede the creation of the institutions studied and the first years of working, besides being a period that social issues have assumed large proportions and the education of adolescents and adults´ analphabets have showed a government obligation. This research has used as source documents produced by and about the educational institutions in focus , as the school file and newspaper articles published in the city on the period subject of the study as well as municipal, state and federal laws relating to adult education. At first is made a balance from academic productions at the data bank CAPES 'thesis on the topic of adult education on historical perspective. Subsequently, based on studies on the historical, social, cultural and anthropological perspectives, presents a discussion about the concepts of literacy and illiteracy, and the relationships which they establish with the ideological-cultural factors, with economic and urban development, and the relationship between orality and writing, types of languages and different cultures. Running along the dissemination of Adolescents and Adults´ Education Campaign in São Carlos and the great number of speeches that was diffused in the newspapers about illiteracy and education, this research concluded that the claims about the adult literacy reflected the national exaltation of the period, as well as the linking of education to social ascension, the national progress, modernity and civility of people, in other words the education as redeemer of the nation's problems. Broaching the creation of night school groups and examining their structural and ...

Este trabalho tem como proposta de pesquisa, a (re) construção da história dos grupos escolares noturnos Eudóxia Coelho e Perpétua Genofre de São Carlos, SP, duas instituições criadas em 1948 que marcaram o início da institucionalização da educação de adultos no município. O recorte temporal privilegiado refere-se às décadas de 1930 a 1950, compreendendo os anos que antecedem a criação das instituições estudadas e os primeiros anos de seus funcionamentos, além de ser um período em que as questões sociais assumiram grandes proporções e a educação de adolescentes e adultos analfabetos se apresentou, sobretudo como uma tarefa do Estado. Essa pesquisa utilizou como fonte a documentação produzida pelas e sobre as instituições escolares em foco, como o arquivo escolar e artigos de jornais em circulação no município no período, bem como as legislações municipal, estadual e federal relativas à educação de adultos. Num primeiro momento faz-se um balanço das produções acadêmicas junto ao banco de teses da CAPES sobre o tema educação de adultos na perspectiva histórica. Posteriormente, com base em estudos sob as perspectivas históricas, sociais, culturais e antropológicas, apresenta-se uma discussão em torno das concepções de alfabetismo e analfabetismo e as relações que elas estabelecem com os fatores ideológico-culturais, com o desenvolvimento econômico e urbano, bem como a relação entre oralidade e escrita, tipos de linguagens e diferentes culturas. Perpassando pela disseminação da Campanha de Educação de Adolescentes e Adultos em São Carlos, SP e pelos inúmeros discursos que se difundiam nos jornais sobre o analfabetismo e a educação, esta pesquisa conclui que, as reivindicações acerca da alfabetização da população adulta refletia a efervescência nacional do período, assim como a vinculação da escolarização à ascensão social, ao progresso nacional, a modernidade e a ...
Keywords: Educação; Educação - Historia; Educação de adultos; Escolas; Analfabetismo; Education